Non-noble metal-nitride based electrocatalysts for high-performance alkaline seawater electrolysis - Yu, Luo (Nat Commun, 2019)
Seawater is one of the most abundant natural resources on our planet. Electrolysis of seawater is not only a promising approach to produce clean hydrogen energy, but also of great significance to seawater desalination. The implementation of seawater electrolysis requires robust and efficient electrocatalysts that can sustain seawater splitting without chloride corrosion, especially for the anode. Here we report a three-dimensional core-shell metal-nitride catalyst consisting of NiFeN nanoparticles uniformly decorated on NiMoN nanorods supported on Ni foam, which serves as an eminently active and durable oxygen evolution reaction catalyst for alkaline seawater electrolysis. Combined with an efficient hydrogen evolution reaction catalyst of NiMoN nanorods, we have achieved the industrially required current densities of 500 and 1000 mA cm(−2) at record low voltages of 1.608 and 1.709 V, respectively, for overall alkaline seawater splitting at 60 °C. This discovery significantly advances the development of seawater electrolysis for large-scale hydrogen production.